Obowiązki przedsiębiorcy w zakresie lokalizacji inwestycji mieszkaniowej i inwestycji towarzyszącej - Brzezińska-Rawa, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The subject of analysis of this article is the issue of linking and analysing the impact of legal regulations in the field of spatial planning, resulting from the special housing law, with the obligations of undertakings. The author analyses legal requirements related to the location of a residential investment and an associated investment. These are infrastructure and distance requirements, as well as requirements to prohibit location in legally protected areas. The historical thread of so-called developer obligations is also included.
Keywords: spatial planning; special law on housing; obligations of undertakings; economic activity